PENGEMBANGAN MEDIA PEMBELAJARAN IPAS BERBASIS DIORAMA DENGAN MENGGUNAKAN SABUT KELAPA PADA SISWA KELAS IV SD NEGERI 106163 BANDAR KLIPPA - Ima Kurniati Dongoran; Zainuddin; Wildansyah Lubis; Lala Jelita Ananda; Suyit Ratno (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study was motivated by students’ low understanding of Natural and Social Sciences (IPAS), particularly on natural resources material, due to the use of conventional teaching methods and limited learning media. This research aims to develop a diorama-based learning media using coconut fiber and to determine its feasibility, practicality, and effectiveness in improving students’ learning outcomes. This study employed a Research and Development (R&D) method using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The research was conducted at SD Negeri 106163 Bandar Klippa with 25 fourth-grade students as the subjects. Data were collected through observation, interviews, questionnaires, and tests. The results showed that the developed diorama media was categorized as highly feasible based on expert validation, including material experts (86%), test experts (85%), media experts (86%), and education practitioners (94.6%). The media was also considered practical for classroom use. In terms of effectiveness, there was a significant improvement in students’ learning outcomes, indicated by an increase in the average pretest score from 46.46 to 79.3 in the posttest, and learning mastery improved from 16% to 100%. In conclusion, the coconut fiber-based diorama learning media is feasible, practical, and highly effective in improving elementary school students’ learning outcomes on natural resources material.